Utilizing ambulatory electrocardiogram monitoring to reduce conduction related death after transcatheter aortic valve replacement. Issue 4 (1st December 2021) - Okoh, Alexis K.; Chen, Chunguang; Kassotis, John; Soliman, Fady; Patel, Kush; Sohitliv, Amy; Loi, Amandeep; Smith, Meghan; Pineda‐Salazar, Jennifer; Chaudhary, Ashok; Ghosh, Bobby D.; Hakeem, Abdul; et al.
Abstract: Objective: The purpose of this study is to assess the utility of ambulatory cardiac monitoring (ACM) in detecting delayed advanced conduction abnormalities (DACA) and associated 30‐day mortality. Background: DACA are well‐known complications of TAVR and may be associated with post‐discharge mortality within 30‐days. Methods: Between October 2019 and October 2020, TAVR patients who were discharged home without a permanent pacemaker (PPM) were monitored with an ACM device for 14‐days. The incidence of DACA at follow up, mortality and readmission within 30‐days were investigated. The risk of DACA was assessed in three patient categories based on a composite of their 12‐lead electrocardiogram (ECG) data. Group I: Normal pre‐TAVR, periprocedural, and discharge ECGs. Group II: Normal pre‐TAVR and abnormal subsequent ECGs. Group III. Abnormal baseline and abnormal subsequent ECGs. Results: Among 340 TAVR patients, 248 were discharged home with an ACM device. The overall incidence of DACA was 7% ( n =  17), of whom 4% ( n =  10) required a PPM. Mortality and readmission between discharge and 30 days was 0% and 8.3%, respectively. Stratification of patients identified 96 (38.7%) patients in Group I: 50 (20%) in Group II, and 102 (41%) in Group III. The incidence of DACA requiring a PPM was 0% in Group I, 4% ( n =  2) in Group II, and 8.5% ( n =  8) in Group III ( p  < 0.004). Conclusions: In TAVR patients who were discharged home with ACM, none died between discharge and 30‐days. For those with normal baseline, perioperative and discharge ECG, there were no events of DACA at 14‐days.